سؤال العلمنة من المسار الإبستيمولوجي إلى الحدث الأنطولوجي في فكر عبد الوهاب المسيري - ربوح البشير (International Institute of Islamic Thought, 2014)
يتمحور البحث حول مفهوم العَلمانية عند المفكر الموسوعي عبد الوهاب المسيري، رحمة الله عليه، من جهة التنقيب عن حركية المفهوم في تاريخ الحداثة الغربية؛ إذ انتقل المفهوم من عَلمانية جزئية إلى عَلمانية شاملة، وَفق متتالية تصاعدية تبدأ من الدين، والاقتصاد، والفلسفة، والوجدان والأحلام، والحياة الخاصة، تماشياً مع الحدث الإبسيمولوجي الذي ينبني على آلية الترشيد المادي، ثم مع الحدث الأنطولوجي الذي يتساكن في وقائع متكثرة مثل: اللباس، والمنـزل، والجسد، ونمط الغذاء، وأفلام الحركة، وأفلام الكارتون... وغيرها، فيحدث ترابط بينهما، سيؤثر على الفكر الغربي الـمُعلمن، وعلى الفكر العربي الذي ما زال يفكر داخل أفق الحداثة. This paper addresses the concept of secularism in the thought of the late thinker Abdel Wahab El-Messiri, particularly examining the dynamism of the concept in the history of Western modernity.  The concept has shifted from partial secularism to total secularism, passing through consecutive processes starting from religion, economics, philosophy, sentiment (conscience), dreams, and private life issues, in accordance with the epistemological event that is based on the mechanism of material rationalization, then with the ontological event associated with a multiplicity of factors, such as dress, habitation, the physical body, eating habits, action films, cartoons, etc.  This results in a strong correlation between the processes, which ultimately affects secularized Western thought, and also Arab thought, which continues to think from within the sphere of modernity.